The role of justice in the procedure and conclusion of ADR and the judicial process - Rivas Caso, Gino (2017)
In the face of a conflict, citizens can follow different ways to solve it. But, how justice is configurated in the conclusion of a specific conflict? what guarantee that the procedure of the mechanism is fair? We can think here in the due process of law; nevertheless, due process of law does not reach all mechanisms of conflict resolution.This paper, therefore, focuses in the study of the role of justice in (i) the procedural scope of judicial process and ADR mechanisms; and in (ii) the conflict resolution generated by them.